Multi-omics analyses reveal fecal microbial community and metabolic alterations in finishing cattle fed probiotics-fermented distiller’s grains diets - Rong Zhang; Shihui Mei; Guangxia He; Miaozhan Wei; Lan Chen; Ze Chen; Min Zhu; Bijun Zhou; Kaigong Wang; Zhentao Cheng; Chunmei Wang; Erpeng Zhu; et al. (Microbiology Spectrum)
ABSTRACT Distiller’s grains (DG) are a potential source of animal feeds, and many studies have indicated positive regulatory roles of feeding DG diets in animal breeding. However, there is currently a dearth of research on the actions and underlying mechanisms of probiotics-fermented distiller’s grains (FDG)-based diets in cattle breeding. This study aimed to assess the impact of integrating FDG into the diet of finishing cattle on their fecal microbial community and metabolites. Thirty Simmental crossbred cattle (local yellow cattle × Simmental cattle, 8.5 months old, 420.38 ± 68.11 kg) were selected and randomly divided into three dietary treatments, including the basal diet group (CON group), the FDG replacing 10% concentrate (FDG-10%) group, and the FDG replacing 20% concentrate (FDG-20%) group. 16S and ITS sequencing of fecal samples collected from each group on the 30th day of the formal feeding suggested that feeding FDG diets had little effect on the composition and diversity of fecal bacterial and fungal communities in finishing cattle. However, the relative abundance of cellulose-degrading bacteria, including the Christensenellaceae R-7 group and Ruminococcaceae family was significantly higher in both the FDG-20% vs CON comparison and the FDG-20% vs FDG-10% comparison. Besides, the FDG-10% group had a significant drop in the relative abundance of Aspergillus and a noteworthy increase in the relative abundance of Candida when compared to the CON group. Non-targeted metabolomics analysis showed that the addition of FDG modified the levels of organoheterocyclic compounds, lipids and lipid-like molecules, and benzenoids in the feces of finishing cattle and significantly enhanced the metabolic pathway of bile secretion. Further correlation analyses suggested a close association between the significantly differential fecal microbiota and metabolites. In conclusion, these results suggest that FDG supplementation has little effect on the structure and diversity of the fecal microbiota in finishing cattle, but alters intestinal metabolite profiles and influences bile secretion pathways by modulating the relative abundance of genera of fecal bacteria and fungi Christensenellaceae R-7 group, Lachnospiraceae_NK3A20_group, Mucor, and Candida. These findings provide a scientific theoretical basis for the use of FDG in animal feeds.IMPORTANCEProbiotics-fermented distiller's grains (FDG) are potential feed sources for livestock. Here, we investigated the effects of partially replacing concentrates with FDG on fecal bacterial and fungal community structure and metabolic profiles in finishing cattle. The results reveal that feeding FDG-based diets alters intestinal metabolite profiles and up-regulates bile secretion pathways through the regulation of relative abundance of certain fecal genera. These findings provide some new insights into clarifying the role and potential mechanisms of FDG diets and also offer a scientific basis for the development of FDG into functional feed resources.